Antiretroviral activity and cytotoxicity of novel zidovudine (AZT) derivatives and the relation to their chemical structure - Turk, Gabriela Julia Ana (2002)
Zidovudine (AZT) was the first nucleoside analogue licensed for the treatment of HIV infection. Efforts have continuously been made to improve the therapeutic characteristics of this drug, most of them focussed on prodrugs design. Here we describe the anti-HIV-1 activity and cytotoxicity of six novel AZT derivatives namely 3′-azido-3′-deoxy-5′-O-oxalyl-N-valinethymidine, 3′-azido-3′-deoxy-5′-O-oxalyl-N-leucinethymidine, 3′-azido-3′-deoxy-5′-O-oxalyl-N-isoleucinethymidine, 3′-azido-3′-deoxy-5′-O-oxalyl-N-phenylalaninethymidine, 3′-azido-3′-deoxy-5′-O-oxalylthymidine acid, 3′-azido-3′-deoxy-5′-O-isonicotinoylthymidine and 5-chloro-6-hydroxy-5,6-dihydro-3′-azido-3′-deoxythymidine which were perfectly characterized. AZT-Val, AZT-Leu, AZT-iLeu, AZT-Phen, AZT-Ac and AZT-Iso have shown a similar or higher selectivity index than that of AZT itself, in one or both of the different cell cultures used (PBMC and MT2). However, AZT-ClOH showed no anti-HIV activity. These results suggest that using amino acids in the design of AZT derivatives improves AZT activity.